QIP on Improving Access to Physical Health Pathways, Services, and Resources for Inpatients in KMPT - Olubunmi Olure; Maham Zahid; Hussein Al-Siraj; Tonye Ajiteru; Chiara Rubino (BJPsych Open)
Aims: Mental health patients are often severely unwell presenting with significant risks to their health and multi-morbidity/complex health needs. Currently, at KMPT there is a lack of access to the right care at the right time with a lot of silo mentality and fragmented services. Feedback from junior doctors includes: